'A nobleman should be clean and smell good': olfactory visuality and haptic space in Aleksei Gherman Sr.'s Hard To Be A God. (2nd September 2018) - Luca, Raymond De
ABSTRACT: This article expands on existing scholarship concerning the olfactory aesthetics of the filmmaker Aleksei Gherman Sr. (1938–2013). Critics have argued that Gherman odorizes his moving images to probe his spectators' memories of the Soviet past. Given the unique spatial properties of stench, however, Gherman's onscreen evocation of smell cannot only be conceived temporally, but must also be theorized spatially. This article puts Gherman's filmography into dialogue with contemporary smell theory to interrogate how his pungent aesthetics effect the production of cinematic space. It reveals a phenomenological correspondence between smell and cinema in that both virtually and emotionally transport the seemingly stationary smeller/spectator to otherwise inaccessible spatio temporalities. If Gherman's earlier work whisks his audiences back to the redolent sites of Stalinism, his last film, Hard to Be a God (2014), launches viewers into the foul-smelling cosmos. Its putrid smellscape, unlike those of Gherman's previous works, generates a haptic space sustained without an over-reliance on the sort of visual and aural proximity conventionally thought necessary for haptic viewing. Hard to Be a God thus expands our notion of embodied visuality. Its overpowering stench, moreover, forwards Gherman's philosophic critique of modern configurations of sanitation in Western modernity.